Nilai Pendidikan Agama Hindu Dalam Lontar Siwa Sasana - Ida Bagus Putu Eka Suadnyana; I Putu Ariyasa Darmawan (Cetta: Jurnal Ilmu Pendidikan, 2020)
Hinduism in addition to giving teachings also guides its people to achieve happiness and harmonize their lives physically and spiritually. Efforts to maintain the preservation of Religion can be done through strengthening education in the field of religion. For people in Bali this is the basic capital as a mental and spiritual driving force and is a guide, guide and impetus in humans to achieve a better and perfect quality of life. The teachings of Hinduism are based on the Vedic scriptures, but also in secondary books, one of which is the ancient manuscripts in the form of Lontar. Dealing with this, the author intends to examine in depth in terms of the value of Hindu religious education for a lontar, namely lontar "Shiva Sasana" which is a religious literary work that is currently only in demand by a small portion of the community or less attention from the younger generation of Hindus. Theories used to solve research problems are convergence theory and value theory. This research is in the form of a qualitative design with data collected with literature study techniques and interpretive methods. After the data collected the data were analyzed with descriptive analysis techniques. The teachings contained in the Lontar Shiva Sasana based on the writer's findings include the teachings of Shivaism and the teachings of the Trikaya Parisudha and the values ​​contained in the Lontar Shiva Sasana include the ethical values ​​and devotional values.